Blowing the bloody doors off [large type] : and other lessons in life - Caine, Michael (Hachette Books, 2018)
One of our best-loved actors, Michael Caine has starred in over 100 films in his six-decade career, spanning classic movies like Alfie, Zulu, and The Italian Job (the inspiration for the book title) to playing Alfred opposite Christian Bale's Batman in Christopher Nolan's blockbuster Dark Knight trilogy. Caine has excelled in every kind of role--with a skill that's made it look easy. Caine knows what success takes. He's made it to the pinnacle of his profession from humble origins. But as he says, "Small parts can lead to big things. And if you keep doing things right, the stars will align when you least expect it." Still working and more beloved than ever, Caine now shares everything he's learned-and "his fans will be rewarded, as will anyone seeking an enjoyable, inspirational read" (Library Journal).